Government’s Role in Advancing Innovation - Yaron Katz (RIRAI Publisher, 2021)
The paper examines the way that policy of governmental intervention can promote innovation and achieve a leading role in global markets. Innovation is a major driver of economic development and what drives competition in modern age, allowing nations a competitive position through investments in technology. The nature of innovation changed significantly in the last decades, and it is today based on technological advancement and openness to global developments. As the world is changing, competition between countries accelerates, and the role of governments in technology development is critical. The paper argues that the most significant role in innovation is provided by governments, which need to create new markets rather than just supervise them. Israel is a leader in innovation, providing the perfect example for the success of governmental policy to encourages innovation. The country is known as the “Start-up Nation”, which means that its economic growth is linked to technology and innovation. This policy promotes innovation by the government, which is deeply involved in the market and dictates the scope of technological advancement.